Nitrous oxide fluxes in an integrated crop-livestock-forestry system - Nogueira, Anna Karolyne da Silva; Rodrigues, Renato de Aragão Ribeiro; Silva, Jacqueline Jesus Nogueira da; Botin, Andressa Alves; Silveira, Júlia Graziela da; Mombach, Mircéia Angele; Armacolo, Natassia Magalhães; Romeiro, Sara de Oliveira (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the mitigation potential of nitrous oxide in an integrated crop-livestock-forestry system (ICLF), compared with monocultures, and to identify the main factors that regulate the emissions of this gas. The experiment was conducted in the municipality of Sinop, in the state of Mato Grosso, Brazil, between the 2012/2013 and 2013/2014 crop seasons, with the evaluation of the following treatments: forest, crop and pasture, besides ICLF. During the experiment, no cattle were present in the pasture areas. Nitrous oxide samples were collected weekly using top-down static chambers. Gas concentrations were determined with gas chromatography. Rainfall and N availability were main factors regulating N2O emissions. The ICLF system has promising potential to mitigate N2O emissions, with 0.367 kg ha-1 N accumulated emission, compared with 1.401 kg ha-1 from cropland, 0.298 kg ha-1 from pasture, and 0.165 kg ha-1 from forest.